Engineering Lactococcus lactis as a cell factory for the production of limonene - Shaili, Nurul ‘Aishah; Song, Adelene Ai Lian; Othman, Sarah; Lian, Lionel Aun In; Abdullah, Janna Ong; Abdul Rahim, Raha (Penerbit Universiti Kebangsaan Malaysia, 2022)
Limonene is a plant monoterpene which contributes significantly to the scent of most essential oils due to its pleasant fragrance. The compound had been reported to have anti-cancer properties against several types of cancer including colorectal cancer. However, the production of this compound in nature is limited because it is produced as a secondary metabolite. To overcome these challenges, Lactococcus lactis was developed as a heterologous host for the production of limonene. A synthesized limonene synthase (LS) from Mentha spicata (mint) was cloned into L. lactis NZ9000. Western blot analysis using mouse IgG His-Tag monoclonal antibody showed successful LS expression by L. lactis at the size of ~55 kDa. GC-MS analysis results showed that limonene production was optimum after 24 h of induction (~8.0 ppm). Metabolic engineering was attempted to enhance the limonene production by overexpression of lactococcal 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) and mevalonate kinase (mvk) genes in the bacterial host. The recombinant L. lactis carrying pNZ:LSMM plasmid successfully enhanced the limonene production to two-fold (~15.1 ppm) after 24 h of induction. The outcomes of this study show the potential of L. lactis to produce plant proteins and bioactive compounds production, which prospectively leads to an oral delivery system for anti-cancer compounds.